The project management of production harvesting with stochastic modeling of three object system - Ковальчик, Юрій Іванович; Тимочко, Василь Олегович; Говда, Оксана Ігорівна (Eastern-European Journal of Enterprise Technologies, 2012)
Results of probability calculation of system standing of three units of harvest equipment in discrete conditions at project management of agricultural production harvesting are described